Effects of methylphenidate on height, weight and blood biochemistry parameters in prepubertal boys with attention deficit hyperactivity disorder: an open label prospective study - Çevikaslan Ahmet; Parlak Mesut; Ellidağ Hamit Yaşar; Kulaksızoğlu Sibel Çilingiroğlu; Yılmaz Necat (Scandinavian Journal of Child and Adolescent Psychiatry and Psychology, 2021)
Background: Adverse effects of stimulants on growth in children have long been studied, but the results remain to be clarified, because metabolic changes or predictors accompanying the growth deviations were not sufficiently studied.